DIAGNÓSTICO AMBIENTAL DAS ÁREAS DE PRESERVAÇÃO PERMANENTE (APP), MARGEM ESQUERDA DO RIO UBERABINHA, EM UBERLÂNDIA (MG) - Brandão, Sélis Luiz; Lima, Samuel do Carmo (Caminhos de Geografia, 2002)
The areas of permanent preservation (APP) they are recognized as fundamental to guarantee the preservation of the quality of the waters, vegetation and fauna, as well as for the dissipation of erosive energy. The legislation recognizes your importance as agent of regulation of the fluvial course, consequently of the floods and, preservation of the sanitary conditions for the development of the human life in the cities. In spite of your importance is noticed in those areas intense degradation process as; drainage, deforestation, garbage deposition, dumps, pastures, etc.